Software Quality - Kaur, Sukhvir (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In the given paper I present the information regarding quality metrics. Different quality factors can be imposing with relation to cost, schedule and rework. It’s very important to make quality assurance plans. For that you have to cover many milestones which can be represented in time sheets. The main characteristics of the quality models have covered in this paper